The Transmission of Oil and Food Prices to Consumer Prices – Evidence for the MENA Countries - Ansgar Belke; Christian Dreger (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
This paper investigates the effects of global oil and food price shocks to consumer prices in Middle East-North African (MENA) countries using threshold cointegration methods. Oil and food price shocks increase domestic prices in the long run, whereby the impact of food prices dominates. While global prices are weakly exogenous, consumer prices respond to deviations from the equilibrium relationship. The short run adjustment pattern exhibits asymmetries and is particularly strong after positive shocks. Downward rigidities on wages may play a crucial role in this regard, as the relatively weak reactions of consumer prices after negative shocks are related to labour market institutions and public subsidies. The more rigid the regulations the more pronounced are the asymmetries. Robustness checks show that international price shocks do not aff ect GDP growth. – – Dieser Beitrag untersucht den Effekt globaler Öl- und Nahrungsmittelpreisschocks auf Konsumentenpreise in Mittel- und Nordafrika im Rahmen einer nicht-linearen Kointegrationsanalyse. Langfristig erhöhen Öl- und Nahrungsmittelpreisschocks die inländischen Preise, wobei der Einfluss der Nahrungsmittelpreise dominiert. Globale Preise erweisen sich dabei als schwach exogen und Verbraucherpreise passen sich an das langfristige Gleichgewicht an. Kurzfristig zeigen sich asymmetrische Anpassungsreaktionen. Die Anpassung ist besonders stark nach positiven Schocks. Nach unten rigide Löhne dürften bei dieser Anpassung eine Schlüsselrolle spielen, da die schwache Reaktion der Verbraucherpreise nach negativen Schocks im Zusammenhang mit arbeitsmarktlichen Regelungen und öffentlichen Transfers steht. Je stärker die Regulierung in diesem Bereich, umso deutlicher treten Asymmetrien hervor. Robustheitstests zeigen, dass die internationalen Preisschocks keinen Einfluss auf das BIP-Wachstum haben.
Keywords: C22; E31; Q02; 330; oil and food price transmission; asymmetric error correction; MENA region